106k views
3 votes
Evaluate the following:

Evaluate the following:-example-1

2 Answers

4 votes

Answer:


\large\boxed{((-2)/(3))/(6)/((-3)/(5))/(10)=(50)/(27)}

Explanation:


((-2)/(3))/(6)/((-3)/(5))/(10)=\left((-2)/(3)/6\right)/\left((-3)/(5)/10\right)=\left((-2\!\!\!\!\diagup^1)/(3)\cdot(1)/(6\!\!\!\!\diagup_3)\right)/\left((-3)/(5)\cdot(1)/(10)\right)\\\\=\left(-(1)/(9)\right)/\left(-(3)/(50)\right)=(1)/(9)\cdot(50)/(3)=(50)/(27)

User Chris Bandy
by
4.8k points
2 votes

Answer:

50/27

Explanation:

User Marcelocra
by
5.7k points